Redesain User Interface pada Website Pudam Banyuwangi Menggunakan Metode User Centered Design - Rahma, Rara Dwi; Haq, Endi Sailul; Panduardi, Farizqi (Sekolah Tinggi Ilmu Komputer PGRI Banyuwangi, 2024)
PUDAM Banyuwangi is a regional public company that provides clean water services to the community with branches in several areas. The PUDAM Banyuwangi website was built with the aim of making company information and services more accessible. It is known, during the creation of the website the company did a refresh which was carried out almost every five years to improve the functionality of the website. however, user experience testing has never been carried out measurably on the website user interface. initial testing was carried out using the User Experience Questionnaire (UEQ) as a user experience measurement tolls by getting results from 51 respondents showing the value of user experience on the website on 6 components, namely attractiveness (-0.12), clarity (0.15), efficiency (0.11), accuracy (-0.04), stimulation (-0.07), novelty (-0.29) so that it falls into the